Screen-based sedentary behaviors, mental health, and social relationships among adolescents - Silva, Danilo R; Werneck, André O; Tomeleri, Crisieli M; Fernandes, Rômulo A; Ronque, Enio Rv; Cyrino, Edilson S (Universidade Estadual Paulista, 2017)
AbstractAim:To analyze the association between screen-based sedentary behaviors, mental health, and social relationships in Brazilian adolescents.Methods:A representative sample of the adolescents from Londrina/PR was selected (n = 1,158; 10 to 17 y). Weekday and weekend screen time (TV-viewing and computer/video-game), mental health indicators (self-rated health, stress, feelings of sadness, and satisfaction with own body), and perceived social relationships (friends, family, and teachers) were collected through questionnaires. Somatic maturation, body mass index, and physical activity were assessed as covariates.Results:Adolescents who reported higher TV-viewing presented higher odds (p < 0.05) for poor self-rated health (boys), higher stress (both sexes), and dissatisfaction with own body (boys), friendships (girls), and teachers (girls). In contrast, higher computer/video-game use was associated with lower odds (p < 0.05) for poor self-rated health (girls), higher stress (boys), feelings of sadness (both sexes), and dissatisfaction with friends (both sexes) and family (both sexes).Conclusion:While higher TV-viewing is associated with negative outcomes, higher computer/video-game users demonstrate better mental health and lower satisfaction with their social relationships.
Keywords: motor activity, physical inactivity; psychological health; interpersonal relations